Improving the Seventh-Grade Students’ Speaking Ability Through Fishbowl Game at SMP Muhammadiyah I Genteng Academic Year - Yayah Ikhda Nevia; Noor Faridha (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
most important thing in therriculum. The result of learning English for junior high school is communication between oral and written. The limitation is the ability to understand sentences in English. Refers to the KTSP curriculum or the education unit-level curriculum. The emphasis in this curriculum is on speaking and writing skills. Ability here can be interpreted as a limitation of literacy function, namely that students are able to interpret and make texts in the form of procedure text, recount text, narrative text, and descriptive text. Procedure text is used to tell about making, or doing something. Often the students find it difficult to do that. The students find it difficult to learn and cannot express again, the teacher must find an easy and effective way, The problem in this research is